Revision of Carapichea (Rubiaceae-Psychotrieae) in the Guianas, with two new combinations and transfer of three species to Notopleura - Olivier Lachenaud; Piero Delprete (Plant Ecology and Evolution, 2022)
Background and aims – The genus Carapichea (Rubiaceae), recently resurrected and separated from Psychotria, currently includes 24 Neotropical species and is morphologically heterogeneous. A revision of the genus in the Guianas is presented here, as part of the authors’ work on the Rubiaceae treatment in the Flora of the Guianas series.Material and methods – This paper is based on a study of herbarium specimens from BBS, BM, BR, BRB, CAY, INPA, K, P, P-JJR, and U; type specimens from other herbaria were consulted online. Some of the species were also studied in the field by the authors. Normal practices of herbarium taxonomy have been applied.Results – Three species previously included in Carapichea (C. altsonii, C. nivea, and C. sandwithiana) show aberrant characters for the genus and are transferred to Notopleura; new combinations are published for the former two (N. altsonii and N. nivea). Eight species of Carapichea, one of them still imperfectly known, are recorded from the Guianas; a ninth species, C. araguariensis, is included in this revision as it is expected to occur in the region. New combinations are published for two species: Carapichea galbaoensis and C. squamelligera, based on Psychotria galbaoensis and P. squamelligera, respectively; the former species was previously included in synonymy of C. guianensis, which is here redefined in a narrower sense. The delimitation of C. ligularis is expanded to include C. pacimonica as a synonym. The first records of C. adinantha in French Guiana – and the Guiana Shield – are documented. The taxonomy of the two remaining species, C. tillettii and C. urniformis, is left unchanged. For every species a complete description is presented, as well as data on distribution, ecology, phenology, local names (when known), and a list of collections studied.